Assessment of Hyperglycemic Potentials of Khaya Anthotheca Stem-Bark Extracts on Alloxan-Induced Diabetic Rats - Umaru, Kerenhappuch Isaac; Nanmar, Chakfa; Umaru, Isaac John; Ugoeze, Egeonu Stephen; Tansaba, Akafa Andes; David, Bando Christopher (Darul Yasin Al Sys, 2024)
Introduction: Medicinal plants have been the basis of treatment of various diseases in African traditional medicine as well as other forms of treatment from diverse cultures of the world. Khaya anthotheca is a member of the family Meliaceae, a native to Africa. It is a medicinal plant widely used for several therapeutic purposes. Herein, phytochemical study, hyperglycaemic investigations was carried out on the methanol extract of Khaya anthotheca Stem-bark. Materials and Methods: However, 35 rats were distributed into seven groups to evaluate the anti-diabetic activity of K. anthotheca stem-bark methanol extract at the dosage range of 50-400 mg/kg/b.wt. The analysis was done using the software-SPSS one-way ANOVA at a significance level p<0.05. Results: The result of the anti-diabetic study reveals that extract elicited substantial (p<0.05) inhibition of hyperglycaemic. The plant Khaya anthotheca stem-bark methanol extract displayed profound (p<0.05) anti-hyperglycaemic action at the dosage of 200 mg/kg/b.wt, 300 mg/kg/b.wt. and 500 mg/kg/b.wt. against induced diabetic rats. Conclusion: This study therefore suggests the use of Khaya anthotheca as a hypoglycaemic agent and for treatment of diabetic. Further studies are needed to discover the bioactive constituent of the plant responsible for this anti-diabetic activity.